Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1175/mwr-d-12-00186.1
|View full text |Cite
|
Sign up to set email alerts
|

A Global Climatology of Baroclinically Influenced Tropical Cyclogenesis

Abstract: Tropical cyclogenesis is generally considered to occur in regions devoid of baroclinic structures; however, an appreciable number of tropical cyclones (TCs) form in baroclinic environments each year. A global climatology of these baroclinically influenced TC developments is presented in this study. An objective classification strategy is developed that focuses on the characteristics of the environmental state rather than on properties of the vortex, thus allowing for a pointwise ''development pathway'' classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 106 publications
7
55
0
1
Order By: Relevance
“…Finally, if a storm does not move at least 10 degrees in latitude over its whole life cycle, no transition is recorded even if one 'appears' in the CPS CA because this is not reconcilable with understandings of ET as the process of storms of tropical genesis moving into the midlatitudes. By implementing these constraints results were considerably improved, for example removing the higher latitude baroclinically induced TCs (McTaggart-Cowan et al, 2013) and monsoonal storms in the northern Indian Ocean that superficially resemble ET in the CPS.…”
Section: Determination Of Etmentioning
confidence: 99%
“…Finally, if a storm does not move at least 10 degrees in latitude over its whole life cycle, no transition is recorded even if one 'appears' in the CPS CA because this is not reconcilable with understandings of ET as the process of storms of tropical genesis moving into the midlatitudes. By implementing these constraints results were considerably improved, for example removing the higher latitude baroclinically induced TCs (McTaggart-Cowan et al, 2013) and monsoonal storms in the northern Indian Ocean that superficially resemble ET in the CPS.…”
Section: Determination Of Etmentioning
confidence: 99%
“…Besides the possible impacts of the NAO, extratropical frontal systems may affect Atlantic TC activity by contributing to TC formation, which is known as the tropical transition Bosart 2003, 2004;McTaggart-Cowan et al 2013). Notably, the tropical transition is often accompanied by potential vorticity (PV) streamers associated with anticyclonic Rossby wave breaking (RWB) (Davis and Bosart 2004;Galarneau et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental factors that are favorable for TC development are well documented and include warm sea surface temperatures (SSTs), moist conditions in midlevels, strong divergence in upper levels, weak vertical wind shear, and preexisting low-level cyclonic vorticity (e.g., Gray 1968;DeMaria et al 2001). It is known, however, that TCs also develop in environments with moderate to strong deep-layer vertical wind shear (e.g., Bracken and Bosart 2000;Davis and Bosart 2001, 2002, 2003 and over relatively cool SSTs (e.g., McTaggart-Cowan et al 2006). In fact, previous research has demonstrated that half of all TC developments over the North Atlantic occur in environments with moderate to strong baroclinicity and attendant vertical wind shear (e.g., McTaggart-Cowan et al 2008, 2013Hess et al 1995;Elsner et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is known, however, that TCs also develop in environments with moderate to strong deep-layer vertical wind shear (e.g., Bracken and Bosart 2000;Davis and Bosart 2001, 2002, 2003 and over relatively cool SSTs (e.g., McTaggart-Cowan et al 2006). In fact, previous research has demonstrated that half of all TC developments over the North Atlantic occur in environments with moderate to strong baroclinicity and attendant vertical wind shear (e.g., McTaggart-Cowan et al 2008, 2013Hess et al 1995;Elsner et al 1996). These baroclinically influenced TC developments encompass subtropical cyclones that undergo tropical transition (TT; e.g., Bosart 2003, 2004;Evans and Guishard 2009;Guishard et al 2009;Hulme and Martin 2009a,b) and precursor low-level cyclonic vorticity centers that interact with upper-tropospheric troughs (e.g., Sadler 1976Sadler , 1978Lander 1994;Molinari et al 1995;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%